Mycorrhizal Mediated Partitioning of Phosphorus: Ectomycorrhizal (Populus x canescens x Paxillus involutus) Potential to Exploit Simultaneously Organic and Mineral Phosphorus Sources - Schreider, Katharina; Hofmann, Diana; Boy, Jens; Andrino, Alberto; Fernandes Figueiredo, Aline; Sauheitl, Leopold; Guggenberger, Georg (Frontiers in Soil Science, 2022)
Many natural and anthropogenic soils are phosphorus (P) limited, as P is largely immobilized in forms of low bioavailability. One of the strategies to overcome this shortage lies in the symbiosis of plants with mycorrhizal fungi, increasing the plant P uptake of these hardly accessible sources. Therefore, mycorrhizal fungal mediated partitioning of differently available P forms could contribute to more efficient use of P by plants, reducing competition for soil P. This study aimed to investigate the uptake of P from differently bioavailable P sources by ectomycorrhizae. For that, we conducted a rhizotrone study using Populus x canescens and its compatible ectomycorrhizal fungus Paxillus involutus. Four different P sources (ortho-phosphate (oP), adenosine monophosphate (AMP), hydroxyapatite (HAP), and oP bound to goethite (gP)) or only HAP as 1P control were supplied in separate compartments, where only the fungal partner had access to the P sources. The amount of the specific P sources was increased according to their decreasing bioavailability. In order to distinguish between the P sources, we applied 33P to track its incorporation in plants by a non-destructive analysis via digital autoradiography. Our results show that an ectomycorrhizal plant is able to utilize all provided P sources via its mycobiont. The acquisition timing was determined by the most bioavailable P sources, with oP and AMP over HAP and gP, and a mixed P pool over single P source. In contrast, the magnitude was defined by the amount of supplied P source and provision of additional nitrogen, hence AMP over oP and gP, as well as by P source complexity, with gP as the least favourable P form. Nevertheless, the results of the present study provide evidence that under not competing conditions an ectomycorrhizae has the potential to be a generalist, whereas according to the nutrient niching theory a specialization to one or a few specific P forms occurs due to the need to compete for limited resources.